2021
DOI: 10.1061/(asce)ww.1943-5460.0000629
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Orientation and Arrangement of Structures on Tsunami Impact Forces: Numerical Investigation with Smoothed Particle Hydrodynamics

Abstract: This paper explores the influence of onshore structures' orientations and arrangements during tsunami impact using the numerical method of smoothed particle hydrodynamics (SPH). Observations from previous tsunami events often reveal variation in the damage and survivability of impacted similar structures. Such variation can be due to shielding effects and other interactions that occur when the tsunami wave is incident upon an urbanised location. The SPH model used in this work was first validated against previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Regularly applied methods that have been used in the tsunami interaction studies are the Finite Volume method [45][46][47], the Arbitrary Lagrangian-Eulerian method [48], the Finite Element method [49], the coupled FEM and meshless method [50,51], the coupled FEM and FVM methods [52] and particle-based methods, such as the Smoothed Particle Hydrodynamics [53], the Moving Semi-Implicit method and the Meshless Local Petrov Galerkin method [50,54]. With increasing computational resources in recent decades, numerical simulations can provide a more in-depth understanding of flow interaction processes [55,56]. From the range of available methods, the open-source FVM solver OpenFOAM is applied in the present study to investigate the interaction processes between tsunamis and inland structures in the presence of seawalls.…”
Section: Introductionmentioning
confidence: 99%
“…Regularly applied methods that have been used in the tsunami interaction studies are the Finite Volume method [45][46][47], the Arbitrary Lagrangian-Eulerian method [48], the Finite Element method [49], the coupled FEM and meshless method [50,51], the coupled FEM and FVM methods [52] and particle-based methods, such as the Smoothed Particle Hydrodynamics [53], the Moving Semi-Implicit method and the Meshless Local Petrov Galerkin method [50,54]. With increasing computational resources in recent decades, numerical simulations can provide a more in-depth understanding of flow interaction processes [55,56]. From the range of available methods, the open-source FVM solver OpenFOAM is applied in the present study to investigate the interaction processes between tsunamis and inland structures in the presence of seawalls.…”
Section: Introductionmentioning
confidence: 99%
“…Cunningham et al (2014) has also demonstrated the suitability of SPH modelling to predict the tsunami wave force on discrete, non-orthogonal structures in comparison to the corresponding experimental results by Zhang (2009). More recently, Pringgana et al (2021) confirmed that the SPH numerical modelling using DualSPHysics was capable of predicting the tsunami wave and structure interaction for an array of structures reproducing and extending the experiments conducted in a large wave basin by Thomas et al (2015).…”
Section: Introductionmentioning
confidence: 57%
“…Generally, the SPH pressure distribution over a surface of a structure is measured by numerical probes. Pressures measured on a surface can be multiplied by the area of structure's surface to obtain force, as described in Pringgana et al (2021). The inter-particle spacing of a group of measuring pressure probes and their distances from the surface of structures are sensitive to the resulting numerical prediction so that prior sensitivity studies are required to achieve numerical pressure predictions comparable to the experimental data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations